Abstract Number ‐ 41: A Comparison of the Safety and Efficacy of Endovascular Techniques in Treating Basilar Tip Aneurysms - Yasmin Ghochani; Sukhdeep S Khurana; Paul Kang; Andrew F Ducruet (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Basilar‐tip aneurysm (BTA) is the most common aneurysm found in the posterior fossa circulation, representing 5–8% of the total intracranial aneurysms. Endovascular techniques are first‐line for treatment of the vast majority of posterior circulation artery aneurysms because of their deep location and the high mortality and morbidity associated with open surgical clipping. Coil embolization (CE) is considered safer and more efficacious in the treatment of BTAs compared to open surgery but has increased rate of recanalization. Twoadjunctivemodifications of CE ‐balloon remodeling techniques(BRT) and stent‐assisted coiling (SAC) ‐ are availableto address the occlusion needs of BTAs of variable anatomies/morphologies, sizes, and rupture status.We aimed to compare the clinical utility, safety and efficacy of these adjuvant therapies for treating BTAs. Methods We conducted a retrospective review of the Barrow Neurological Institute (BNI) endovascular database from January 1996 through January 2019. Primary outcomes were obliteration as assessed by the modified Raymond Score (MRS), perioperative complications, recurrence, retreatment, and time to 1stretreatment. Secondary outcomes were stratification of the results based on rupture and wide‐neck status and the type of stent. Results 121 patients with an average follow‐up of 43.4 months were included. Ruptured aneurysms were more likely to be treated by CE vs. either adjuvant therapy (p< 0.001), and SAC was the preferred treatment for larger aneurysms (p = 0.004). SAC had significantly worse obliteration (MRS of 2.09±0.94) vs. BRT (MRS of 1.82±0.91; p = 0.038) but was less likely to be retreated as compared to BRT (35.3%; p = 0.047). However, SAC had a shorter time to first retreatment 13.4±13.8 months as compared to the BRT (25.3±26.7 months) and CE (50.3±68.5 months; p = 0.04 and 0.006, respectively). Lastly, SAC had significantly lower recurrence of 31.8% and near‐significantly lower retreatment rate of 27.3% (p = 0.045, 0.058, respectively) as compared to CE (recurrence of 46.2% and retreatment of 34.6%). There was no significant difference in peri‐operative complications among the three groups. Conclusions CE and its adjuvant therapies have similar safety profile but pose variable efficacy in terms of obliteration, recurrence, retreatment, and durability over time. This study represents one of the largest data sets on endovascular adjuvant therapy of BTAs and has the potential to inform clinical decision making when considering CE with BRT vs. SAC for BTA of specific size and morphology.As future directions, outcomes specifically in the old vs. new stent groups and according to further stratification of the largest dimension of the BTA will need to be analyzed, and we will further interrogate any association between the co‐morbidities, such as smoking status and hypertension, with aneurysm rupture, largest dimension, and wide‐neck status.